Institutions And The Preservation Of Cultural Traits - Anja Prummer; Jan-Peter Siedlarek (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2014)
We offer a novel explanation for why some immigrant groups and minorities have persistent, distinctive cultural traits - the presence of a rigid institution. Such an institution is necessary for communities to not fully assimilate to the mainstream society. We distinguish between different types of institutions, such as churches, foreign-language media or ethnic business associations and ask what level of cultural distinction these institutions prefer. Any type of institution can have incentives to be extreme and select maximal cultural distinction from the mainstream society. If institutions choose positive cultural distinction, without being extremist, then a decrease in discrimination leads to reduced assimilation.
Keywords: 330